2017
DOI: 10.1080/21541248.2017.1313182
|View full text |Cite
|
Sign up to set email alerts
|

Rab GTPases and cell division

Abstract: Cytokinesis is a complex cellular process that leads to a physical separation of two daughter cells. The key to a successful cytokinesis is a coordinated reorganization of cellular cytoskeleton and membrane trafficking pathways. Consequently, Rab GTPases recently emerged as major regulators of cellular division. Rabs belong to a superfamily of small monomeric GTPases that regulate a diverse array of cellular functions. Rabs in particular are well-established regulators of membrane transport and have been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…6A; Supplemental Table S1), which belong to a family of monomeric small GTPases of the Ras superfamily. It has been reported that several Rab GTPases are crucial for cytokinesis and function in regulating cell division (Qi and Zheng, 2013;Gibie za and Prekeris, 2018). Therefore, the response of root elongation in rapeseed to N deficiency might be achieved through a coordination of these relevant proteins involved in both cell division and cell expansion.…”
Section: Discussionmentioning
confidence: 99%
“…6A; Supplemental Table S1), which belong to a family of monomeric small GTPases of the Ras superfamily. It has been reported that several Rab GTPases are crucial for cytokinesis and function in regulating cell division (Qi and Zheng, 2013;Gibie za and Prekeris, 2018). Therefore, the response of root elongation in rapeseed to N deficiency might be achieved through a coordination of these relevant proteins involved in both cell division and cell expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Ras-related protein 6 (RAB6) is a kind of small GTPases which are involved in vesicular traffic in the secretory and endocytic pathways 15 . Rab protein, as a molecular switch of vesicle transport, interacts with its upstream regulatory factors and downstream specific effectors, plays an important role in the formation and transport of vesicles, and a series of Rab effector proteins have been found to be involved in cellular phagocytic and protein transport pathways 16 18 . RAB6 is involved in the composition of the Golgi and cytoplasmic vesicles and regulate protein transport between the Golgi apparatus, endoplasmic reticulum (ER) and endosomes 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Its increased abundance is associated with a higher oxygen supply to gills of trachurus fish, which supports oxidative metabolism and the larger growth phenotype. Rab-GDI regulates Rab GTPases, which control many cellular signaling processes, including those that are involved in membrane trafficking, cell differentiation and proliferation (growth) 23 .…”
Section: Morphotype Fingerprint Proteinsmentioning
confidence: 99%